Symptoms of soil salinity and measures to combat it (Texas Journal of Agriculture and Biological Sciences, 2024)
Soil Salinization Causes & How To Prevent And Manage It. Salinization of soil negatively impacts plant development and induces land degradation. Saline earths show lower agricultural productivity, worsen farmers’ wellbeing, and the economic situation in the region. Managing soil salinity at early stages helps to reverse it. However, heavy contamination leads to complete loss of farmlands and desertification due to the negative effect of salinity on soil properties.